The meaning and challenge of voluntary counselling and testing (VCT) for counsellors - report of the Kenya Association of Professional Counsellors (KAPC) conference for sub-Saharan Africa - Cecilia Rachier; Elias Gikundi; Don Balmer; Maggie Robson; Kathryn Hunt; Nonie Cohen (Taylor & Francis Group, 2004)
A large number of voluntary counselling and testing (VCT) sites are being opened in sub-Saharan Africa. The services provided by these sites are playing an increasingly important role in the prevention of HIV/AIDS. The sites offer many possibilities and it is crucial that they provide the optimum services for clients. Counselling is an integral part of these services, yet it receives little attention. Counsellors need to be consulted if the optimum services are to be provided, but they are rarely consulted for their professional opinion. Accordingly, the Kenya Association of Professional Counsellors (KAPC) organised a 3-day conference in September 2002 to provide counsellors, drawn from the sub-Saharan region, with a forum to identify VCT-related issues and discuss their implications. The main aim of the conference was for counsellors to arrive at a consensual position regarding HIV/AIDS and what improvements they thought could be made for the VCT services to clients. The counsellors identified the issues that they considered important and this paper presents those issues together with recommendations regarding improvements.